Reliability analysis of geosynthetic-reinforced steep slopes - Fernanda Ferreira (2016)
In slope stability analysis, the high degree of uncertainty associated with design parameters has led to increasing use of reliability-based approaches as a means of evaluating the combined effects of such uncertainties on the structure performance. In this study, the reliability level of geosynthetic-reinforced steep slopes designed according to Eurocode 7 (EC7), without any additional margin of safety, was assessed using the commercially available Slide 6.0 software based on Monte Carlo simulation. To validate the EC7 partial factor design method regarding structural reliability, the estimated reliability indexes were compared with the minimum value recommended by Eurocode 0 (EC0). Additionally, through a probabilistic sensitivity analysis, the effect of variability in design parameters on slope reliability was evaluated and discussed. The results have shown that the geosynthetic-reinforced slopes designed to EC7 specifications exhibit generally an adequate reliability level according to EC0. The soil friction angle and the friction angle of the soil-geosynthetic interface and, secondly, the surcharge load, were found to be the most significant parameters for the reliability of the analysed slopes. For typical coefficients of variation of design parameters, the EC7 partial factor method tends to be conservative in terms of structural reliability. However, in situations of abnormal high variability, the partial factor methodology may lead to unsafe design, and thus reliability analyses should be implemented.